How Should the Educational Researcher Speak? Thoughts from a Beginning Researcher (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
Understanding that researchers are already aware of the gap between theory and practice, this article seeks to add to the dialogue, through a look at the gap, relating the gap to effective communication.  The article offers a brief look at effective research, including the perspective as a practitioner, as well as that of a researcher. It is not so much that the practitioner and researcher always have different views on the issues being studied, but that effective communication of the research is essential for the research to be understood and considered.